2014
DOI: 10.1186/1550-2783-11-37
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a multi-ingredient dietary supplement on body composition, adipokines, blood lipids, and metabolic health in overweight and obese men and women: a randomized controlled trial

Abstract: BackgroundThe present study investigated the effects of a multi-ingredient dietary supplement (MIDS) containing caffeine, conjugated linoleic acid (CLA), green tea, and branched-chain amino acids (BCAA) taken for 8 weeks on body composition, blood lipid profile, glucose, insulin, adiponectin, leptin, and high-sensitivity C-reactive protein (hs-CRP) in overweight and obese men and women.MethodsTwenty-two participants completed the study (PL, n = 11; 7 women, 4 men; age, 34 ± 3.5 years; height, 169.2 ± 3.3 cm; b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
(61 reference statements)
0
6
0
1
Order By: Relevance
“…Titles and abstracts of 813 articles were read, and 774 articles were excluded. By considering criteria for inclusion and exclusion, 22 articles were excluded due to following reasons: not having a control group ( N = 3; Alghadir, Gabr, & Al‐Eisa, ; Lee et al, ; Sung et al, ), intervention less than 1 day ( N = 3; Alexopoulos et al, ; Hsu et al, ; Koutelidakis et al, ), and using other nutrients beside green tea in the intervention group ( N = 16; Bakker et al, ; Braga et al, ; Cialdella‐Kam et al, ; de Jesus Romero‐Prado et al, ; Dominiak, McKinney, Heilbrun, & Sarkar, ; Kim et al, ; Madaric et al, ; Nieman et al, ; Nieman et al, ; Ormsbee et al, ; Peluso et al, ; Rondanelli et al, ; Rubio‐Perez, Albaladejo, Zafrilla, Vidal‐Guevara, & Morillas‐Ruiz, ; Scolaro et al, ; Soriano‐Maldonado, Hidalgo, Arteaga, de Pascual‐Teresa, & Nova, ; Thomas, Williams, Sharma, Chaudry, & Bellamy, ; Figure ). Therefore, 17 articles were included in our systematic review (Basu et al, ; Bogdanski et al, ; de Maat et al, ; Dower et al, ; Fukino et al, ; Fukino, Shimbo, Aoki, Okubo, & Iso, ; Gutierrez‐Salmean et al, ; Hu et al, ; Hussain, Habib Ur, & Akhtar, ; Mielgo‐Ayuso et al, ; Mombaini & Jafarirad, ; Nogueira, Nogueira Neto, Klein, & Sanjuliani, ; Oyama et al, ; Oyama, Maeda, Sasaki, et al, ; Ryu et al, ; Shin et al, ; Sone et al, ); because the article by Ryu et al () did not report baseline values, we did not include it in our meta‐analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Titles and abstracts of 813 articles were read, and 774 articles were excluded. By considering criteria for inclusion and exclusion, 22 articles were excluded due to following reasons: not having a control group ( N = 3; Alghadir, Gabr, & Al‐Eisa, ; Lee et al, ; Sung et al, ), intervention less than 1 day ( N = 3; Alexopoulos et al, ; Hsu et al, ; Koutelidakis et al, ), and using other nutrients beside green tea in the intervention group ( N = 16; Bakker et al, ; Braga et al, ; Cialdella‐Kam et al, ; de Jesus Romero‐Prado et al, ; Dominiak, McKinney, Heilbrun, & Sarkar, ; Kim et al, ; Madaric et al, ; Nieman et al, ; Nieman et al, ; Ormsbee et al, ; Peluso et al, ; Rondanelli et al, ; Rubio‐Perez, Albaladejo, Zafrilla, Vidal‐Guevara, & Morillas‐Ruiz, ; Scolaro et al, ; Soriano‐Maldonado, Hidalgo, Arteaga, de Pascual‐Teresa, & Nova, ; Thomas, Williams, Sharma, Chaudry, & Bellamy, ; Figure ). Therefore, 17 articles were included in our systematic review (Basu et al, ; Bogdanski et al, ; de Maat et al, ; Dower et al, ; Fukino et al, ; Fukino, Shimbo, Aoki, Okubo, & Iso, ; Gutierrez‐Salmean et al, ; Hu et al, ; Hussain, Habib Ur, & Akhtar, ; Mielgo‐Ayuso et al, ; Mombaini & Jafarirad, ; Nogueira, Nogueira Neto, Klein, & Sanjuliani, ; Oyama et al, ; Oyama, Maeda, Sasaki, et al, ; Ryu et al, ; Shin et al, ; Sone et al, ); because the article by Ryu et al () did not report baseline values, we did not include it in our meta‐analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…not having a control group (N = 3;Alghadir, Gabr, & Al-Eisa, 2016;Lee et al, 2005;Sung et al, 2005), intervention less than 1 day (N = 3;Alexopoulos et al, 2008;Hsu et al, 2007;Koutelidakis et al, 2014), and using other nutrients beside green tea in the intervention group (N = 16;Bakker et al, 2010;Braga et al, 2012;Cialdella-Kam et al, 2016;de Jesus Romero-Prado et al, 2015;Dominiak, McKinney, Heilbrun, & Sarkar, 2010;Kim et al, 2016;Madaric et al, 2013;Nieman et al, 2013;Nieman et al, 2017;Ormsbee et al, 2014;Peluso et al, 2014;Rondanelli et al, 2013;Rubio-Perez, Albaladejo, Zafrilla, Vidal-Guevara, & Morillas-Ruiz, 2016; Scolaro et al, 2018; Soriano-Maldonado, Hidalgo, Arteaga, de Pascual-Teresa, & Nova, 2014; Thomas, Williams, Sharma, Chaudry, & Bellamy, 2014; Figure 1).Therefore, 17 articles were included in our systematic review(Basu et al, 2011;Bogdanski et al, 2012;de Maat et al, 2000;Dower et al, 2015;Fukino et al, 2008;Fukino, Shimbo, Aoki, Okubo, & Iso, 2005;Gutierrez-Salmean et al, 2016;Hu et al, 2016;Hussain, Habib Ur, & Akhtar, 2017;Mielgo-Ayuso et al, 2014;Mombaini & Jafarirad, 2017;Nogueira, Nogueira Neto, Klein, & Sanjuliani, 2017;Oyama, Maeda, Sasaki, et al, 2010;Ryu et al, 2006;Shin et al, 2018;Sone et al, 2011)…”
mentioning
confidence: 99%
“…A total of 79 potential relevant articles and 14 trials were retrieved for further assessment. Six of these studies, however, were excluded from the analysis because four of them [ 11 , 13 , 27 , 28 ] incorporated CLA as part of the active components in treatment group, one adopted an RCT with no double-blind design [ 19 ], and the other one used a cross-over RCT design with short intervention duration (3 weeks) [ 20 ]. Meanwhile, one study separately determined BP in overweight and obese subjects and was considered as two trials [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…While these factors may be affected by increased levels of adiposity, previous studies have demonstrated that protein supplementation and exercise training may favorably combat obesity-related cardiovascular and metabolic risks [ 13 , 19 , 40 ]. In the current study, there were similar reductions in systolic blood pressure, total cholesterol, low-density lipoprotein cholesterol, leptin, insulin, and blood glucose concentrations, as well as an increase in adiponectin concentrations in both groups ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%